2014
DOI: 10.1038/ejhg.2014.144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of previously unrecognized FAP in children with Gardner fibroma

Abstract: Fibromatous soft tissue lesions, namely desmoid-type fibromatosis and Gardner fibroma, may occur sporadically or as a result of inherited predisposition (as part of familial adenomatous polyposis, FAP). Whereas desmoid-type fibromatosis often present b-catenin overexpression (by activating CTNNB1 somatic variants or APC biallelic inactivation), the pathogenetic mechanisms in Gardner fibroma are unknown. We characterized in detail Gardner fibromas diagnosed in two infants to evaluate their role as sentinel lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…FAP must be excluded in a child with fibromas suggestive of Gardner syndrome because de novo variants can occur in patients with a negative family history, as seen in this patient and other cases (Levesque et al 2010). However, diagnosis may also identify previously unrecognized FAP families (Vieira et al 2015), so genetic testing of parents and siblings is a critical part of the evaluation process.…”
Section: Discussionmentioning
confidence: 99%
“…FAP must be excluded in a child with fibromas suggestive of Gardner syndrome because de novo variants can occur in patients with a negative family history, as seen in this patient and other cases (Levesque et al 2010). However, diagnosis may also identify previously unrecognized FAP families (Vieira et al 2015), so genetic testing of parents and siblings is a critical part of the evaluation process.…”
Section: Discussionmentioning
confidence: 99%
“…In all the other patients, patients who presented a GAF plus a positive family history of FAP and constitutional APC mutations were identified. Later, Vieira et al., focused on the role of GAF as a sentinel of FAP. The authors described two infants with both GAF and a previously unrecognized familial history of FAP.…”
Section: Discussionmentioning
confidence: 99%
“…Given that GAF had recently been identified as a potential sentinel of familial adenomatous polyposis (FAP) , the molecular analysis of the APC gene on constitutional DNA was performed in our patient by Sanger sequencing and by multiple ligation‐dependent probe amplification (SALSA MLPA kit P043 APC, lot. C1‐1212).…”
Section: Case Reportmentioning
confidence: 99%
“…Viera et al reported two infants with GF which led to previously unrecognized FAP in the families. 11 In their patients, immunofluorescent staining of β-catenin in the tumor, which accumulates in cells with biallelic truncation of APC because of the impairment of APC-mediated degradation of βcatenin, 4 led to the strong suspicion of underlying FAP. This may well be a future diagnostic tool in evaluating the role of GF in detection of FAP.…”
Section: Discussionmentioning
confidence: 99%